2013
DOI: 10.3109/10641963.2012.758273
|View full text |Cite
|
Sign up to set email alerts
|

Ovariectomy Causes Overexpression of Renal Na+,K+-ATPase and Sodium-Sensitive Hypertension in Adult Wistar Rats

Abstract: We investigated the effect of ovariectomy(oVx) on renal and systemic hemodynamic, electrolyte excretion and total and dephosphorylated Na(+),K(+)-ATPase α1 subunit (t-d-NKA) in normotensive Wistar rats under a normal sodium (NS, 0.24%) or high sodium (HS, 1%) intake versus intact female (IF). On NS intake, t-d-NKA was higher in oVx rats and overexpressed in the thick ascending limbs (P < .01 vs. IF) and renal plasma flow was increased. On HS intake, oVx rats maintained a greater dephosphorylated NKA, excreted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…In agreement with our previous findings (Di Ciano et al., 2013), the present results show that oVx adult Wistar rats when exposed to high sodium load are not able to excrete sodium as IF HS rats do. Consequently, while IF HS rats remain normotensive, oVx HS rats develop salt‐sensitive hypertension.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In agreement with our previous findings (Di Ciano et al., 2013), the present results show that oVx adult Wistar rats when exposed to high sodium load are not able to excrete sodium as IF HS rats do. Consequently, while IF HS rats remain normotensive, oVx HS rats develop salt‐sensitive hypertension.…”
Section: Discussionsupporting
confidence: 94%
“…In previous work, we found that ovariectomized adult Wistar rats under high salt (HS) intake develop HT (Di Ciano et al., 2013). Thus, the absence of female sex hormones together with high sodium induced an increase in BP in this model of salt‐sensitive hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Two days before clearance studies subgroups of HS rats (IF and oVx) were treated with the D1-like receptor antagonist SCH 23390 [1 mg/kg body wt sc twice a day; R (ϩ)-SCH 23390 hydrochloride, Sigma-Aldrich, St. Louis, MO] or with vehicle (normal saline). Animals were anesthetized with Inactin (50 mg/kg body wt ip) and surgically prepared for a renal clearance experiment as described previously (13). The trachea was cannulated to facilitate breathing.…”
Section: Methodsmentioning
confidence: 99%
“…Further results showed that ovariectomy causes an overexpression of the total Na ϩ -K ϩ -ATPase (t-NKA) ␣1-subunit in tubular epithelial cells as well as an altered balance between the phosphorylation/dephosphorylation of NKA to a more dephosphorylated (more active) state. As a consequence, when ovariectomized (oVx) rats were shifted from a normal-sodium diet (NS) to a high-sodium diet (HS), they were unable to achieve a normal sodium balance and developed salt-sensitive hypertension (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation